Performance evaluation of maximum-likelihood page detection for 2-D interference channel - Li, Kwok Hung (2013)
The issue of maximum-likelihood page detection (MLPD) of a two-dimensional (2-D) interference channel corrupted by additive white Gaussian noise is studied. A new way of analyzing the performance of MLPD is proposed which provides a distinct understanding of the MLPD for 2-D interference channels. An approximated bounding method is also proposed which can accurately predict the performance bound while greatly reducing the computational complexity.